To what extent is climate change included in South African District Municipality Integrated Development Plans: A review of IDPS between 2011 and 2021 - Windell, Warwick Neville (Rhodes University, Faculty of Pharmacy, Pharmacy)
Embargo applied. Embargo period to expire in October of 2027.
Keywords: Uncatalogued